Alternative Solution Of The Dilemma Of Investment Towards Forest Sustainability In Aceh (Indonesia) - Yahya, Azhari; Dahlan, Dahlan; Yusri, Yusri (International Asia Of Law and Money Laundering, 2024)
This article aims to scrutinize the dilemma of investment toward forests in Aceh and to find out anticipatory efforts to overcome investment problems that destroy forests in Aceh. This research was conducted by using qualitative research methods and the necessary data was collected through library research. The results of the study show that investment in Aceh has a positive impact on Aceh's economic growth, but uncontrolled investment has damaged forests and ecosystems in Aceh, causing floods and negative impacts on the local community such as floods and damaging animal ecosystems. The factors causing investments that destroy forests among others are ineffective government policies in managing forests, lack of prevention of investments that destroy forests, and weak legal enforcement in the investment and environmental sectors. To overcome the above dilemma, it is necessary to strengthen regulations and strict law enforcement, promote sustainable forest management, increase public and business awareness, and increase cooperation between related parties. This is important to do to maintain a balance between economic development and environmental sustainability as well as the survival of the local community.